Colorectal Endoscopic Submucosal Dissection in a Western Center: Analysis of Outcomes and Safety Profile - Santos-Antunes, J (2021)
Introduction: Endoscopic submucosal dissection (ESD) is a well-established endoscopic technique for the treatment of gastrointestinal lesions. Colorectal ESD outcomes are less reported in the Western literature, and Portuguese data are still very scarce. Our aim was to describe our experience on colorectal ESD regarding its outcomes and safety profile. Methods: We conducted a retrospective evaluation of recorded data on ESDs performed between 2015 and 2020. Only ESDs performed on epithelial neoplastic lesions were selected for further analysis. Results: Of a total of 167 colorectal ESDs, 153 were included. Technical success was achieved in 147 procedures (96%). The lesions were located in the colon (n = 24) and rectum (n = 123). The en bloc resection rate was 92% and 97%, the R0 resection rate was 83% and 82%, and the curative resection rate was 79% and 78% for the colon and the rectum, respectively. The need for a hybrid technique was the only risk factor for piecemeal or R1 resection. We report a perforation rate of 3.4% and a 4.1% rate of delayed bleeding; all the adverse events were manageable endoscopically, without the need of blood transfusions or surgery. Most of the lesions were laterally spreading tumours of the granular mixed type (70%), and 20% of the lesions were malignant (12% submucosal and 8% intramucosal cancer). Conclusion: Our series on colorectal ESD reports a very good efficacy and safety profile. This technique can be applied by endoscopists experienced in ESD.